Psychological Features of Examination Anxiety in Psychology Students - Скворчевська, Євгенія Леонідівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
The article analyzes the problem of psychological characteristics of examination anxiety among psychology students. The results of the examination anxiety characteristics study are presented. Girls are characterized by a higher test anxiety than boys. During the session period, girls are characterized by a greater emotional distress associated with examination anxiety than boys. The peculiarities of personal and reactive (situational) anxiety of psychology students during the session and in the intersessional period were studied. Young men are characterized by lower values of personal and situational (reactive) anxiety than girls. For girls, these indicators are on the threshold between the average and high levels of anxiety. In general, the boys in the sample are more anxious than the girls. The specificity of examination anxiety of different sex’s psychology students with different academic performance has been studied. In boys, the level of examination anxiety, interferes with achievement, is significantly lower than in girls. This allows us to conclude that it is in girls, in contrast to boys, that examination anxiety is found, which negatively affects the results of activity during the preparation for tests and exams and passing the test and examination tests. The revealed level of examination anxiety in most cases stimulates and promotes the activities of young men in the period of preparation for tests and exams and passing the test and examination tests than girls. The interrelationships of examination anxiety indicators with indicators of personal and reactive anxiety, success and motivation of students have been studied. Among the dominant motives of educational motivation in the group of young men, avoidance, communicative and professional motives prevail. For girls, educational activity is directed by professional and educational-cognitive motives. Correlation analysis showed that psychology students, whose educational activity is directed to avoidance motives, are characterized by less anxiety and show less anxiety about exams, in contrast to students with educational and cognitive motivation. Psychology students, whose educational activity is guided by a professional motive, are characterized by less anxiety.